Activation-enhanced α(IIb)β(3)-Integrin–Cytoskeleton Interactions Outside of Focal Contacts Require the α-Subunit - Kucik, Dennis F. (The American Society for Cell Biology, 2001)
Integrins link the cell's cytoskeleton to the extracellular matrix, as well as to receptors on other cells. These links occur not only at focal contacts but also at smaller integrin-containing protein complexes outside of focal contacts. We previously demonstrated the importance of focal contact-independent integrin–cytoskeleton interactions of β(2) integrins: activation of adhesion resulted from a release of integrins from cytoskeletal constraints. To determine whether changes in integrin–cytoskeleton interactions were related to activation of the integrin, we used single particle tracking to examine focal contact-independent cytoskeletal associations of α(IIb)β(3)-integrin, in which activation results in a large conformational change. Direct activation of α(IIb)β(3) by mutation did not mimic activation of lymphocytes with phorbol ester, because it enhanced integrin–cytoskeleton interactions, whereas activation of lymphocytes decreased them. Using additional integrin mutants, we found that both α- and β-cytoplasmic domains were required for these links. This suggests that 1) both β(2)- and β(3)-integrins interact with the cytoskeleton outside of focal contacts; 2) activation of a cell and activation of an integrin are distinct processes, and both can affect integrin–cytoskeleton interactions; and 3) the role of the α-subunit in integrin–cytoskeleton interactions in at least some circumstances is more direct than generally supposed.